Paired vagus nerve stimulation for post-stroke shoulder motor recovery: corticospinal–C5 motor network plasticity and rehabilitation applications - Xiang Ji; Weiran Zheng; Wei Ma; Jiaying Liu; Guizhi Xu (Frontiers in Neurology, 2026)
Shoulder motor impairment after stroke restricts reaching, self-care, balance reactions, and the use of mobility aids. Paired vagus nerve stimulation (pVNS), in which brief cervical vagus nerve stimulation is temporally coupled to task-specific rehabilitation, improves overall upper-extremity impairment and activity in selected people with chronic ischemic stroke. Its shoulder-specific effects, however, remain uncertain. This Mini Review evaluates pVNS through a corticospinal–C5 motor-network frameworkthat links movement-related cortical ensembles, descending corticospinal and reticulospinal pathways, cervical C5 motor pools, and the peripheral motor units controlling the supraspinatus, deltoid, infraspinatus, and scapular stabilizers. Preclinical studies show that appropriately timed pVNS recruits noradrenergic, cholinergic, and serotonergic systems, promotes movement-specific motor-cortical plasticity, and augments forelimb recovery after experimental stroke. Randomized clinical trials demonstrate durable improvement in composite upper-limb outcomes, leading to regulatory approval for moderate-to-severe arm impairment after chronic ischemic stroke. Nevertheless, secondary analyses indicate a clearer treatment advantage for distal than proximal components, and shoulder abduction has not been tested as an independent primary endpoint. We therefore outline a candidate shoulder-focused rehabilitation model combining graded antigravity abduction, external rotation, scapular control, and functional reaching with defined stimulation pairing and multimodal monitoring. The model presupposes an intact peripheral C5 motor unit: pVNS cannot repair complete C5-root, upper-trunk, suprascapular, or axillary nerve denervation. Shoulder-specific trials incorporating kinematics, electromyography, transcranial magnetic stimulation, and tract imaging are required before efficacy for proximal recovery can be claimed.